A comparison of the behavior of C57BL/6 and C57BL/10 mice. - Deacon, R; Thomas, C; Rawlins, J; Morley, B (2007)
Selection of an appropriate animal model is a crucial first step in many research programs. The C57BL/6 (B6) mouse is the most widely used inbred mouse strain in biomedical research; this is particularly so in behavioral studies. However, there are several C57BL substrains, all derived from common ancestors. C57BL/10 (B10) mice are superficially almost identical to B6 mice in appearance and behavior and widely used in inflammation and immunology research, yet rarely in behavioral studies. The present study assessed the comparability of behavioral results from these two strains, to determine whether they could be used interchangeably in future behavioral experiments. The results showed that the behavior of B6 mice clearly differed from that of B10 mice: in tests of cognition, species-typical behaviors, and motor coordination the B6 strain performed better. Consequently, B6 mice will probably remain the preferred choice for behavioral studies. Interpretation of results derived from the B10 strain should take into account its particular behavioral characteristics.